Druse clinopyroxene in D'Orbigny angritic meteorite studied by single-crystal X-ray diffraction, electron microprobe analysis and Mössbauer spectroscopy - Abdu, Yassir A. (2009)
The crystal structure of druse clinopyroxene from the D'Orbigny angrite, (Ca0.944 Fe 2+ 0.042 Mg0.010Mn0.004) (Mg0.469Fe 2+ 0.317Fe 3+ 0.035Al0.125Cr0.010Ti0.044) (Si1.742Al0.258) O6, a = 9.7684(2), b = 8.9124(2), c = 5.2859(1) A, β = 105.903(1)°, V = 442.58 A 3 , space group C2/c, Z = 2, has been refined to an R1 index of 1.92% using single-crystal X-ray diffraction data. The unit formula, calculated from electron microprobe analysis, and the refined site scattering values were used to assign site populations. The distribution of Fe 2+ and Mg over the M1 and M2 sites suggests a closure temperature of 1000 °C. Mossbauer spectroscopy measurements were done at room temperature on a single crystal and a powdered sample. The spectra are adequately fit by a Voigt-based quadrupole-splitting distribution model having two generalized sites, one for Fe 2+ with two Gaussian components and one for Fe 3+ with one Gaussian component. The two ferrous components are assigned to Fe 2+ at the M1 site, and arise from two different next-nearest-neighbor configurations of Ca and Fe cations at the M2 site: (3Ca,0Fe) and (2Ca,1Fe). The Fe 3+ /Fetot ratio determined by Mossbauer spectroscopy is in agreement with that calculated from the electron microprobe analysis. The results are discussed in connection with the redox and thermal history of D'Orbigny.